Recruitment Model Proposal for IT Manager with SWARA, ARAS and GRA Methods - Ali Sevinç; Aşır Özbek; Şeyma Nur Aydın (Sakarya University Journal of Computer and Information Sciences)
In the information age, one of the most strategic departments for modern businesses is the information technology department. Modern businesses receive the necessary support from the information technology department to keep up with the digital age and follow technological developments. Therefore, managers working in these departments must have the necessary skills in both informatics and management. In this study, a model was proposed using multi-criteria decision-making methods for the selection of an information technology manager for a food company. In the first stage of the model, criteria were determined according to the test subjects applied by the company under different titles to measure the professional and academic knowledge of the applicant candidates and the criteria were weighted with the SWARA method. In the second stage, an objective decision matrix was created by using the test scores of the candidates. In the last stage, the best candidate for the company was determined with the ARAS and Gray Relational Analysis method. The greatest contribution of the study to the literature is to show the applicability of a model that combines the objective decision matrix and subjective evaluations.